The Effectiveness of the Garut Intan Application in Providing Information on Homecoming and Returning Flows in the Garut Police Legal Area - Toriq Akbar Tulus (Tanggon Kosala, 2020)
This research is motivated by the issue of traffic discussed congestion published in the area with the level of complexity of the activity, challenges at the peak or could have occurred because of traffic capacity (demand) that is not proportional to the volume of the road (supply) besides that there are also modes available mixed, and also at certain times such as the celebration of certain religious holidays. One of the traffic issues related to land transportation that is quite complicated to overcome in various regions is the minimum ability to provide road network infrastructure, while the intensity of vehicle flow can be improved. This situation causes many accidents, accidents and traffic jams on various city roads. Literature research about research conducted on student research that discusses the case of a traffic accident. which researchers can support the process of making the thesis of the writer. As for the conceptual literature, the author uses Management Theory by George R. Terry and concepts related to the title that the writer adopts. This research was conducted using qualitative methods, using descriptive analysis, and data collection techniques by interviewing, observing, and studying documents. The results of the study found that the support in supporting or supporting the Garut Intan Application as a whole understood to use for supervision as well as supporting the application. The Garut Intan application is not only an application for providing information about past congestion, but is also related to providing important places on the way such as gas stations, police stations, hospitals that can send information through applications that are fast and will be related agencies. Users of the Garut Intan Application are very satisfied with the service of this application, and the community who use this application will continue to grow in accordance with information needs at the time of going home and back flow in 2020